(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. Digital transformation brings numerous advantages, but also gives rise to complex ethical and social dilemmas, especially in the economic domain. In response, companies are compelled to develop their own standards and regulatory approaches to the management of digital technologies and data processing. In this context, the concept of Corporate Digital Responsibility (CDR) plays a significant role, representing a modern extension and specification of Corporate Social Responsibility (CSR) adapted to the digital age. Purpose. Considering the specificity of the media industry, this study aims to examine the general concept of CDR and analyze the relevance and applicability of its implementation in the media sector. Methods. The article employs methods of analysis and synthesis of academic literature, systematization, and theoretical generalization. Results. It is established that corporate digital responsibility in media refers to the independent decision-making of media organizations (media enterprises and digital platforms) regarding a responsible approach to the implementation and use of digital technologies and the treatment of clients at every stage of media content production and distribution. This is based on accepted principles, values, and norms aimed at filling legal gaps, protecting stakeholders, and meeting societal expectations. The concept of CDR encompasses the following responsibility areas: digital governance, digital transparency, digital empowerment, digital capital, and digital inclusion. It has been proven that the involvement of media users in the creation of new products and the reassessment of existing ones, automation, and the use of AI for task planning, data analysis, and content creation have blurred the lines between product and service, information and advertisement, content creator and consumer. This blurring prompts specific ethical and social issues. In the economic context, the main challenges relate to media product creation and copyright ownership, data collection and processing, equal access to information, and the opportunity to participate in public discourse. It is argued that due to the inability of legislation to rapidly regulate the media digitalization process and the emerging dilemmas, media enterprises should adopt the CDR concept to promote a responsible organizational culture. Conclusion. There is growing public demand for a responsible approach to digitalization in the media. A positive response to this demand will strengthen public trust in companies that implement such practices.